Fevicordin A and Fevicordin A Glucoside, Novel Norcucurbitacins from Fevillea cordifolia - Achenbach, Hans (1987)
From the seeds of the Central American Fevillea cordifolia (Cucurbitaceae) fevicordin A glucoside (1) and fevicordin A (2) members of the novel norcucurbitacin group, were isolated.